PENGARUH QUANTUM LEARNING DAN PENGGUNAAN MEDIA TIGA DIMENSI TERHADAP MINAT BELAJAR SISWA - Intan Nadiroh (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2019)
Abstract: Quantum learning is a strategy in teaching and learning activities that have unique, fun, and fun characteristics. So, in student learning is not directed to stressful or tense thinking but rather to enjoy, besides that it also uses the media to accelerate the delivery of messages from teacher to student. Therefore, to realize high interest in students' souls, a combination of various aspects is needed, some of which are media, strategies, techniques, and so on. The focus of this research is to find out a) Is there any influence of quantum learning on increasing student interest in the material of volume cube and beam class V MI Mamba'ul Ma'arif Denanyar Jombang, b) Is there an influence of the use of three-dimensional media on increasing student interest in cube volume and class beam material V MI Mamba'ul Ma'arif Denanyar Jombang, c) Is there any influence of quantum learning and the use of three-dimensional media to increase student interest in learning the volume of cube volumes and blocks in class V MI Mamba'ul Ma'arif Denanyar Jombang. To answer the problem formulation, this research uses multiple linear regression analysis test and classic assumption test with the help of SPSS 20 for windows. This research is included in quantitative research with multiple regression type, which uses random sampling techniques. The total sample was 45 students (13 male and 32 female). The results of this study stated that there are effects of the two independent variables on the dependent variable. This can be known from the results of calculations using the t-test and f test, with the following details: a) There is a significant influence between the three-dimensional media on student learning interest, this can be proven by the results of T arithmetic = 2.313> 2,000 with probability ( ?) 0.026 <0.050, b) There is a significant influence between the three-dimensional media on student learning interest, this can be proven by the results of T arithmetic = 2.963> 2,000 with a probability (?) 0.005 <0.050, c) There is a significant influence between three-dimensional media of student learning interest, this can be proven by the results of F arithmetic = 10.388> 3.22 with a probability (?) 0.000 <0.050.